2005
DOI: 10.1111/j.0038-4941.2005.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnic Differences in Nonspecific Psychological Distress: Evidence from the National Health Interview Survey*

Abstract: Objective. This article documents the patterns of white‐nonwhite differences in nonspecific psychological distress and explores how acculturation characteristics, social class, marital status, and chronic illness mediate or moderate these differences for eight racial/ethnic populations in the United States. Methods. We analyze data from a five‐year pool of the National Health Interview Survey (NHIS) collected between 1997 and 2001 (N=162,032) and employ multivariate regression techniques to explore level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
79
4
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(99 citation statements)
references
References 42 publications
12
79
4
3
Order By: Relevance
“…The transcultural validity of standardized scales has been questioned repeatedly but, as discussed previously, the most popular scales used to assess psychological distress (e.g., GHQ and K6 or K10) have shown their construct validity across various ethnic groups. Bratter and Eschbach (Bratter and Eschbach 2005) have used data from the National Health Interview Survey conducted in the United States of America (USA) to investigate the association between ethnicity and psychological distress. The large sample size (n = 162 032) recruited over the five cross-sectional annual waves (from 1997 to 2001) of the survey allowed them to stratify respondents in 10 self-reported "race/ethnic" groups.…”
Section: Socio-demographic Factorsmentioning
confidence: 99%
“…The transcultural validity of standardized scales has been questioned repeatedly but, as discussed previously, the most popular scales used to assess psychological distress (e.g., GHQ and K6 or K10) have shown their construct validity across various ethnic groups. Bratter and Eschbach (Bratter and Eschbach 2005) have used data from the National Health Interview Survey conducted in the United States of America (USA) to investigate the association between ethnicity and psychological distress. The large sample size (n = 162 032) recruited over the five cross-sectional annual waves (from 1997 to 2001) of the survey allowed them to stratify respondents in 10 self-reported "race/ethnic" groups.…”
Section: Socio-demographic Factorsmentioning
confidence: 99%
“…Individuals in such samples are members of the general population who were asked to value a selection of health states from which a model is estimated to predict preferences for all the health states described by the measure. Among such measures are the EuroQol EQ-5D (EQ-5D), Health Utilities Index Mark 2 and Mark 3 (HUI2 and HUI3), Quality of Well-Being Scale (QWB-SA) and SF-6D, which is computed from the SF-36v2 TM or the SF-12v2 TM (FRYBACK et al, 2007a;FRYBACK et al, 2007b, SHAW et al, 2007DEVERILL, 2002;ROBERTS, 2004). These instruments differ somewhat in the health domains they consider and they produce different scores and disutilities (i.e.…”
Section: Health Domainsmentioning
confidence: 99%
“…The NCS results indicate that blacks had lower prevalence rates for the disorders the study assessed (KESSLER et al, 1996). 2 Despite the aforementioned prevalence issues, there is also a large body of literature showing that black Americans have higher rates of psychological distress and depression than whites (SIMPSON et al, 2007), but that relationship becomes less strong, or inverse, when measures of socio-economic status are taken into account (BRATTER; ESCHBACH, 2005;NEIGHBORS, 1986). This purely socioeconomic interpretation became the most widely accepted position, starting in the 1970's, when several studies found that the initial higher levels of distress among blacks were attenuated when social class was taken into account.…”
Section: Mental Health and Racementioning
confidence: 99%
See 2 more Smart Citations